Synoptic 129I and CFC–SF6 Transit Time Distribution (TTD) Sections Across the Central Arctic Ocean From the 2015 GEOTRACES Cruises. Issue 9 (23rd September 2022) - Smith, John N.; Smethie, W. M.; Casacuberta, Nuria
Abstract: Measurements of the tracers, 129 I, CFC‐11, and SF6 on water samples collected in the Arctic Ocean in 2015 have been used to calculate mean ages, Γ and mixing, Δ parameters using transit time distributions (TTDs) to constrain water circulation and mixing time scales. Values of Γ and Δ determined separately using the two tracer pairs, SF6 ‐CFC‐11, and 129 I‐CFC‐11 are in good agreement for gas solubilities estimated for saturation levels of 0.90, but agreement decreases for other gas saturation levels. Both Γ and Δ increase rapidly with increasing depth below the base of the intermediate water layer (ca. 1, 000 m), but maintaining a value of Δ/Γ ≅ 1 supporting the use of this proportionality in applications of TTDs to deep ocean transport of substances such as anthropogenic carbon. Isolines of Γ  = 20 years deepening to depths below 1, 000 m over the flank of the Mendeleyev Ridge near the North Pole outline the bathymetrically steered, return flow of recently ventilated Atlantic Water toward Fram Strait. Basin interior waters are significantly older with the Γ  = 25 years mean age isoline shallowing upward to depths above 500 m in the Makarov, Canada, and Eurasian Basins. Values of Δ remain relatively constant in the 6–10 years range in upper intermediate water across all three basins indicating that flow is principally advective and that the mixing specified by Δ likely occurs upstream of the central basins in regions proximal to the outflow from the Santa Anna Trough. Plain Language Summary: Measurements of the tracers, 129 I, CFC‐11, and SF6 on water samples from the Arctic Ocean have been used to calculate mean ages, Γ, and mixing, Δ, parameters using transit time distributions (TTDs) in order to constrain water circulation and mixing time scales. Values of Γ increase with increasing water depth in Atlantic intermediate water and with distance across the Arctic Ocean from the Nordic Seas input region to the Canada Basin. The mixing parameter, Δ, is a metric that relates to the cumulative amount of tracer mixing undergone by a volume element of water. In contrast to Γ, measured values of Δ are relatively constant in arctic intermediate waters indicating strong advective transport throughout the central Arctic Ocean. Values of Γ and Δ determined separately using the tracer pairs, SF6 ‐CFC‐11, and 129 I‐CFC‐11 are in good agreement for gas solubilities at saturation levels of 0.90, but agreement decreases for other gas saturation levels. Both Γ and Δ increase rapidly with increasing depth below the base of the intermediate water layer (ca. 1, 000 m), but maintaining a value of Δ/Γ ≅ 1 supporting the use of this proportionality in applications of TTDs to deep ocean transport of anthropogenic carbon. Key Points: Measurements of 129 I, CFC‐11, SF6 in Arctic Ocean used to calculate mean ages, Γ and mixing, Δ to constrain water circulation time scales Γ sections conform to historical ideas of tracer ages; Δ nearly constant in upper intermediate water indicating strong advective flow High Δ values in upper halocline are congruent with nutrient maximum indicating that both are governed by winter shelf mixing processes